Lessons learned: the use of an augmented reality application in organic chemistry laboratories - Ward, Lyniesha Wright; Spencer, Dan; Chauhan, Daivik; Oliver-Hoyo, Maria (Frontiers in Education, 2024)
Immersive technologies such as augmented reality (AR) have the potential to enable students to remediate invalid assumptions about molecular structure through visualizing site-specific, non-observable chemical processes. In this study, we explore how this technology-embedded instruction impacted student perceptions and experiences in a collaborative face-to-face and independent remote organic chemistry laboratory, the latter of which occurred during the COVID-19 pandemic. While we acknowledge the emotional toll of the pandemic, it afforded a unique opportunity to compare the differences in implementation when covering the same material. We used a novel AR mobile application, H NMR MoleculAR, and a complementary worksheet to support students' understanding of proton nuclear magnetic resonance (1H NMR) spectroscopy. We gathered data using a mixed-methods pre-post survey about students’ perceptions and experiences in the remote and in-person environments. There were differences in student user experience and perceptions of NMR knowledge, with face-to-face students showing more positive rankings. Although lower than those in face-to-face environments, perceptions of the remote environment remained neutral or positive for all measures. There were no differences in the reported number of challenges faced, but there were unique challenges in the remote learning environment. Our findings illuminate the complexity of factors that must be considered when implementing novel technologies into instruction in face-to-face and remote environments. We conclude by describing concrete lessons learned and considerations for researchers and instructors leveraging augmented reality.